2012
DOI: 10.4103/0973-1075.105695
|View full text |Cite
|
Sign up to set email alerts
|

End of life and life after death - issues to be addressed

Abstract: Being an Oncologist, I have seen many patients suffering from cancer. It pains a lot looking at them fighting the battle of life, though knowing that they would lose miserably and surrender meekly as majority of the patients report to the hospital at an advanced stage of disease and only palliative care may be the option. There is an urgent need to create - Cancer Awareness in the villages and also about the end of life care in all terminally ill patients. 20 patients in the terminal phase were questioned rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Population studies have indicated that most people would prefer to die at home. [16][17][18][19][20][21] End-of-life care at home requires a considerable amount of time from a community-based primary care team. The role of the primary care teams is to manage symptoms, provide education, coordinate care, and provide additional or enhanced support and care.…”
Section: Discussionmentioning
confidence: 99%
“…Population studies have indicated that most people would prefer to die at home. [16][17][18][19][20][21] End-of-life care at home requires a considerable amount of time from a community-based primary care team. The role of the primary care teams is to manage symptoms, provide education, coordinate care, and provide additional or enhanced support and care.…”
Section: Discussionmentioning
confidence: 99%
“…Every individual has the right to end life with dignity (1) . This can be maintained when one’s preferences toward end of life are fulfilled (2) , (3) . Among these preferences, place for end-of-life care had become a major issue especially in ageing societies (4) , (5) , (6) .…”
Section: Introductionmentioning
confidence: 99%